FMR studies of half metallic ferromagnetic thin films Co2MnSn and Co2MnGe - Yilgin, R.; Kazan, S.; Rameev, B.; Aktas, B.; Westerholt, K. (Iop Publishing Ltd, 2009)
Thin films of Heusler alloys Co(2)MnSn and Co(2)MnGe prepared on sapphire a-plane substrates by RF-sputtering have been investigated by ferromagnetic resonance (FMR) technique. The magnetic anisotropies of the Co(2)MnSn and Co(2)MnGe thin films have been probed and the effective magnetization values have been extracted. Weak in-plane anisotropies observed for the Co(2)MnGe sample indicate a textured growth of the films. Non-uniform (spin-wave and interface/surface) modes have been observed and the exchange stiffness constants for the Co(2)MnSn and Co(2)MnGe films have been estimated.
International Conference on Superconductivity and Magnetism (ICSM) -- AUG 25-29, 2008 -- Ankara Univ, Side, TURKEY